IMPLEMENTASI PENDELEGASIAN KEWENANGAN BUPATI KEPADA CAMAT STUDI PELAYANAN IZIN MENDIRIKAN BANGUNAN SKALA KECIL DI KECAMATAN KAYAN HILIR KABUPATEN MALINAU - Samion Samion; Adri Patton; Nur Fitriyah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study aims to describe and analyze the Implementation of the Delegation of the Authority of the Regent to the Camat (Study Service License to Build a Small-Scale Building in Kayan Hilir Sub-district, Malinau District). This research includes descriptive research with a qualitative approach. The data analysis technique to be used is data analysis using an interactive model of analysis. The result of the research shows that the Implementation of the Delegation of the Authority of the Regent to the Camat (Study of Small Scale Building Permit Service in Kayan Hilir Sub-district, Malinau District) has not been optimally implemented.Keywords: Implementation, Delegation, Building Permit